Risk assessment of exposure to mycotoxins (aflatoxins and fumonisins) through corn tortilla intake in Veracruz City (Mexico). Issue 6 (3rd June 2019) - Wall-Martínez, H.A.; Ramírez-Martínez, A.; Wesolek, N.; Brabet, C.; Durand, N.; Rodríguez-Jimenes, G. C.; García-Alvarado, M. A.; Salgado-Cervantes, M. A.; Robles-Olvera, V. J.; Roudot, A.C.
ABSTRACT: This study aimed to assess aflatoxin and fumonisin intake through corn tortilla consumption in Veracruz city. Between October 2013 and February 2015, a total of 120 corn tortilla samples (2 kg samples, 40 samples per year) were randomly collected. Aflatoxins and fumonisins were quantified by high performance liquid chromatography coupled with a fluorescence detector. A probability density function (PDF) was used for describing corn tortilla intake, body weight of the Veracruz city population, mycotoxin content of corn tortilla samples and estimated mycotoxin daily intake. The Monte Carlo method with 10, 000 iterations was employed to assess the population exposure risk. The highest level of total aflatoxins (AFT) was 22.17 μg kg −1, and 526.6 μg kg −1 for fumonisins B1 plus B2, with 85% and 90% of contaminated samples respectively. Up to 69.7 % of the population was estimated to consume a higher aflatoxin dose than that recommended by the JECFA (1 ng kg −1 of body weight per day); it was found that the recommended dose was exceeded to a greater extent in the male population, due to higher consumption of corn. The risk of fumonisin intake was less than 5 % due to the low presence and levels of these toxins in corn tortillas . The results suggest that corn tortilla consumers are at dietary risk caused by AFT contamination; this information should be considered when taking action to protect public health. Graphical abstract: